IMPLEMENTATION OF CORPORATE GOVERNANCE AT POSCO - Bahri Sriwijaya, Sayid (Dinasti Publisher, 2020)
Corporate Governance is a structure consisting of shareholders, directors, managers, a set of objectives to be achieved by the company, and tools that will be used in achieving goals and monitoring performance. This study aims to determine the application and benefits of Corporate Governance at POSCO, using descriptive qualitative analysis methods. The application of the principles of Corporate Governance at POSCO has been carried out since 1997 through the management philosophy of